Q: 3.4 x 30 equals

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x-6y=30 y=34-6x substitute the the value for y from the second equation into the first equation. 3x-6(34-6x)=30 3x-204+36x=30 39x-204=30 39x=234 x=234/39 x=6 Substitute this value of x into equation 2. y=34-6(6) y=34-36 y=-2

The answer to the problem of 7-3x equals 34 is x equals -9.

30% off of 34= 30% discount applied to 34= 34 - (30% x 34)= 34 - (0.30 x 34)= 34 - 10.2= 23.80

30 squared is 900. 16 squared 256. add them and you get 1156. Now, simply do: √1156 The answer is 34. Its simple: (30•30)+(16•16)=x^2 900+256=x^2 1156=x^2 √1156=x 34=x

34 x 9=306

Related questions

x + 30 = 64 Therefore, x = 64 - 30 x = 34

4x8=32 32x2=64 64-30=34 X=8

4x² - 30 = 34 4x² = 34 + 30 4x² = 64 4x = √64 4x = 8 x = 8 ÷ 4 x = 2

4x2-30 = 34 4x2 = 34+30 4x2 = 64 x2 = 16 x = 4

Answer : x = ± 1 4x2 - 30 = 34 : 4x2 = 34 - 30 = 4 4x2 = 4 : x2 = 1 therefore x = √1 = ± 1

4x2 - 30 = 34 ⇒ 4x2 = 64 ⇒ x2 = 16 ⇒ x = 4 or -4

y = 28 + ¾x y = 30 + ½x → 28 + ¾x = 30 + ½x → ¾x - ½x = 30 - 28 → ¼x = 2 → x = 2 × 4 = 8 → y = 30 + ½ × 8 = 30 + 4 = 34 → solution is the point (8, 34) (ie x = 8, y = 34)

3x-6y=30 y=34-6x substitute the the value for y from the second equation into the first equation. 3x-6(34-6x)=30 3x-204+36x=30 39x-204=30 39x=234 x=234/39 x=6 Substitute this value of x into equation 2. y=34-6(6) y=34-36 y=-2

34 X 30 is 1020.

The answer to the problem of 7-3x equals 34 is x equals -9.

30% off of 34= 30% discount applied to 34= 34 - (30% x 34)= 34 - (0.30 x 34)= 34 - 10.2= 23.80

30 squared is 900. 16 squared 256. add them and you get 1156. Now, simply do: √1156 The answer is 34. Its simple: (30•30)+(16•16)=x^2 900+256=x^2 1156=x^2 √1156=x 34=x